Formulation and evaluation of solid lipid nanoparticles of a water soluble drug: Zidovudine - Singh S.; Dobhal A.K.; Jain A.; Pandit J.K.; Chakraborty S. (My University, 2025)
The present investigation was undertaken to develop solid lipid nanoparticles (SLN) of a hydrophilic drug Zidovudine (an anti-human immunodeficiency viral agent) and improve the entrapment efficiency of the drug in SLN. The SLN were prepared with stearic acid by process of w/o/w double-emulsion solvent-evaporation method using 32 factorial design. Different triglycerides alone and in different combinations, with/without stearic acid were used to prepare SLN using similar procedure. Two operating variables, polyvinyl alcohol concentration and amount of lipid were found to have significant effect on the particle size and entrapment efficiency (EE) of the SLN. The maximum EE was found to be ca. 27% with particle size of 621 nm which was significantly higher than that reported earlier. The optimized batch was also analyzed for its morphological, physiochemical and drug release properties. EE of batches with triglycerides were significantly less than that achieved with stearic acid alone. This work indicates the possible advantage of fatty acids over triglycerides in the entrapment of hydrophilic drugs in SLN. © 2010 Pharmaceutical Society of Japan.